2022
DOI: 10.3390/plants11141842
|View full text |Cite
|
Sign up to set email alerts
|

Salinity Stress Tolerance in Potato Cultivars: Evidence from Physiological and Biochemical Traits

Abstract: Salinity stress is a major constraint to sustainable crop production due to its adverse impact on crop growth, physiology, and productivity. As potato is the fourth most important staple food crop, enhancing its productivity is necessary to ensure food security for the ever-increasing population. Identification and cultivation of salt-tolerant potato genotypes are imperative mitigating strategies to cope with stress conditions. For this purpose, fifty-three varieties of potato were screened under control and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 72 publications
1
8
0
Order By: Relevance
“…While the uptake of K were decreased in potatoes shoot with W2 and W3 treatments, but the decreased was a positive effected with related increments (39.70 and 34.15 kg acre -1 ); (30.86 and 30.59 kg acre -1 ) and (23.40 and 22.55 kg acre -1 ) of W(1,2,3) + F2 compared with the control treatments (20.32 and 18.25 kg acre -1 ), respectively, in both season. These results are in the same line with those of (Sameh et al, 2019 andSanwal et al, 2022), they reported that spraying potato plants with potassium silicate gave the best values for the estimated elements in leaves of potato plants.…”
Section: Effect Of Various Treatments On Potato Plant Growthsupporting
confidence: 92%
See 1 more Smart Citation
“…While the uptake of K were decreased in potatoes shoot with W2 and W3 treatments, but the decreased was a positive effected with related increments (39.70 and 34.15 kg acre -1 ); (30.86 and 30.59 kg acre -1 ) and (23.40 and 22.55 kg acre -1 ) of W(1,2,3) + F2 compared with the control treatments (20.32 and 18.25 kg acre -1 ), respectively, in both season. These results are in the same line with those of (Sameh et al, 2019 andSanwal et al, 2022), they reported that spraying potato plants with potassium silicate gave the best values for the estimated elements in leaves of potato plants.…”
Section: Effect Of Various Treatments On Potato Plant Growthsupporting
confidence: 92%
“…In semi-arid and growing regions, salinity is one of the abiotic factors that has an impact on potato growth and productivity by changing plant metabolism and significantly affecting biochemical and molecular process (Sanwal et al, 2022). All plant systems and enzymatic processes can be severely disrupted by the accumulation of Na+ and Cl-in cells, which is exceedingly poisonous (Flowers et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In defensive response, the SOD and CAT convert free radical species into H 2 O 2 and oxygen, respectively [ 55 ]. Salt tolerance in tomato, potato, cabbage, and amaranth caused by higher antioxidants activity were also reported [ 48 , 56 , 57 , 58 , 59 ]. A positive correlation between enhanced antioxidant activity and reduced oxidative damage has been observed in the present study.…”
Section: Discussionmentioning
confidence: 92%
“…This might lead to deeper comprehension and an integrated method that incorporates several factors of salt‐adaptive traits. To accurately examine phenotypic traits produced by highly computational modelling of multidimensional data and to offer a more thorough knowledge of the complex mechanisms under salt stress, a combination of analyses must be used (Singh & Sastry 2011; Sanwal et al, 2022). To preserve as much information as possible, PCA, for example, lowers the number of variables in a data collection and uses an orthogonal transformation to turn a set of observations of potentially correlated variables into a set of values of uncorrelated variables (Kumawat et al, 2021; Sabouri et al, 2022).…”
Section: Introductionmentioning
confidence: 99%